Causes of ozone pollution in summer in Wuhan, Central China. (October 2018) - Zeng, P.; Lyu, X.P.; Guo, H.; Cheng, H.R.; Jiang, F.; Pan, W.Z.; Wang, Z.W.; Liang, S.W.; Hu, Y.Q.
Abstract: In August 2016, continuous measurements of volatile organic compounds (VOCs) and trace gases were conducted at an urban site in Wuhan. Four high-ozone (O3 ) days and twenty-seven non-high-O3 days were identified according to the China's National Standard Level II (∼100 ppbv). The occurrence of high-O3 days was accompanied by tropical cyclones. Much higher concentrations of VOCs and carbon monoxide (CO) were observed on the high-O3 days ( p < 0.01). Model simulations revealed that vehicle exhausts were the dominant sources of VOCs, contributing 45.4 ± 5.2% and 37.3 ± 2.9% during high-O3 and non-high-O3 days, respectively. Both vehicle exhausts and stationary combustion made significantly larger contributions to O3 production on high-O3 days ( p < 0.01). Analysis using a chemical transport model found that local photochemical formation accounted for 74.7 ± 5.8% of the daytime O3, around twice the regional transport (32.2 ± 5.4%), while the nighttime O3 was mainly attributable to regional transport (59.1 ± 9.9%). The local O3 formation was generally limited by VOCs in urban Wuhan. To effectively control O3 pollution, the reduction ratio of VOCs to NOx concentrations should not be lower than 0.73, and the most efficient O3 abatement could be achieved by reducing VOCs from vehicle exhausts. This study contributes to the worldwide database of O3 -VOC-NOx sensitivity research. Its findings will be helpful in formulating and implementing emission control strategies for dealing with O3 pollution in Wuhan. Graphical abstract: Highlights: Vehicular emissions were the largest contributor to VOCs in Wuhan. VOCs from vehicular exhausts made the highest contribution to O3 formation. Regional transport accounted for ∼60% and ∼30% of nighttime and daytime O3, respectively. The reduction ratio of VOCs to NOx concentrations should not be lower than 0.73 for effective O3 control. Abstract : Local formation dominated daytime O3, while nighttime O3 was attributable to regional transport in Wuhan.